the Langcat Series. - Dorp & Dal, Gent (Amsterdam : Vous Etes Ici, 1992)
Trockel, Rosemarie ; Rombouts/Droste ; Fortuyn/O'Brien ; Bijl, Guillaume ; Scholte, Rob ; Dokoupil, Jiri Georg ; Ayres, Tim ; Uglow, Alan ; etc.
The Langcat Series, Dorp & Dal, Gent, 21 november tot 20 december 1992
boek